Insight into the relationship between sleep characteristics and anxiety: A cross-sectional study in indigenous and minority populations in northeastern Greece. (October 2020) - Serdari, Aspasia; Manolis, Apostolos; Tsiptsios, Dimitrios; Vorvolakos, Theofanis; Terzoudi, Aikaterini; Nena, Evangelia; Tsamakis, Konstantinos; Steiropoulos, Paschalis; Tripsianis, Gregory
Highlights: Cross-sectional population based study designed in order to evaluate the potential association of sleep characteristics with anxiety disorders in indigenous and minority populations using self-reported questionnaires. Anxiety symptoms are more prominent among minority groups. Anxiety disorders are associated with shorter sleep duration and reduced sleep efficiency Individuals with anxiety exhibit high prevalence of excessive daytime sleepiness, insomnia symptoms, poor sleep quality and risk of obstructive sleep apnea. Abstract: A cross-sectional population-based study was conducted in order to evaluate the association of sleep characteristics with anxiety disorders using self-reported questionnaires and taking into account several socio-demographic, lifestyle and health related characteristics. 957 participants between 19 and 86 years old were enrolled in our study. Anxiety symptoms were assessed using the Zung Self-rating Anxiety Scale. Participants self-reported their daily sleep habits and filled in the following scales: Epworth Sleepiness Scale, Athens Insomnia Scale, Pittsburgh Sleep Quality Index and Berlin Questionnaire. Overall prevalence of anxiety was 33.6%. Anxiety symptoms were more prominent among minority groups. Subjects with anxiety reported shorter sleep duration and reduced sleep efficiency. After adjusting for all possible confounders, they were five times more likely to exhibit short sleep duration (≤6h) and 0.60 times less likely long sleep duration (>8h). These relations remained significant in both genders, but were more pronounced among men. Moreover, anxiety was associated with excessive daytime sleepiness, insomnia, poor sleep quality and higher risk of obstructive sleep apnea (OSA). Results highlight the association of sleep disturbances with anxiety disorders and call for conduction of larger scale prospective studies in order to assess causality on the clinically important relationship between sleep characteristics and anxiety disorders.